Relationship Between Healthy Lifestyle and Fitness Level of Grade V Students of State Elementary School 173360 Sinambela - Manalu , Rizki Bastanta B.; Sejahtra, Sejahtra (Universitas Majalengka, 2025)
Current developments in everyday life, especially for primary school children, neglect healthy lifestyles and physical fitness. Lifestyle is the way a person lives his life, this includes various aspects starting from daily habits. This study aims to determine the relationship between lifestyle and the level of physical fitness of grade v students of SD Negeri 173360 Sinambela. This research is a quantitative study with a non-experimental type of research to test physical fitness. This research uses descriptive correlation analysis method. The research sample with purposive sampling technique using a healthy lifestyle questionnaire research instrument and measurement of fitness level using the multistage fitness test. This research was conducted in SD Negeri 173360 Sinambela in October 2024. The results of the study were that respondents in the good lifestyle category had a fitter physical fitness level compared to students in the regular lifestyle category. There is a significant relationship between healthy lifestyle and fitness level of fifth grade students of SD Negeri 173360 Sinambela